SORPTION OF OIL BY MECHANOCHEMICALY ACTIVATED SHUNGITE - Yerdos Ongarbayev; Moldir Baigulbayeva; Yerbol Tileuberdi; Kairat Zhumakhan (Rudarsko-geološko-naftni Zbornik, 2022)
In the paper the sorption capacity of shungite rocks of the Koksu field (Kazakhstan) in relation to the oil from the Karazhanbas and Tengiz fields (Kazakhstan) were studied. Oil spills occurring during production, gathering, transportation, storage and refining, and repair work on wells are an urgent environmental problem. There are effective methods of soil purification, including particular interests addressed to sorption process. The aim of this research is to study oil sorption by shungite rocks of the Koksu deposit after mechanochemical activation. The mechanochemical activation of shungite rock samples was carried out in a planetary ball mill at different speeds of rotation and ratios of ball mass to the sample. The developed sorbents based on shungite rocks of the Koksu deposit were tested for cleaning samples of oil-contaminated soils and their sorption capacities under dynamic and static conditions were determined. For the sorption of oil, the sorbent based on shungite of shale grade (TS) after mechanochemical activation is recommended, which sorption capacity under dynamic conditions is 2.57-2.85 g/g. Sorption of oil from 10 % of oil contaminated soil samples with the sorbents based on shungite after mechanochemical activation showed sorption capacity of 0.44-0.45 g/g in 60 days under static conditions. The practical significance of the research lies in the prospects of using shungite rocks to clean up oil spills.